The Role of The Tax Court in The Judicial System: Implications of Constitutional Court Decision No. 26/PUU-XII/2023 For Tax Law - Khalimi Khalimi (JURNAL AKTA, 2025)
This article examines the implications of the Constitutional Court Decision No. 26/PUU-XXI/2023 for the Tax Court within Indonesia's judicial system. The decision transfers oversight of the Tax Court from the Ministry of Finance to the Supreme Court, enhancing judicial independence and addressing governance dualism. This study employs a normative legal research methodology to analyze how this ruling fortifies the principles of separation of powers and checks and balances as enshrined in the 1945 Constitution. It highlights the importance of the Tax Court's role in protecting taxpayer rights and ensuring impartiality in tax dispute resolution. The findings underscore the necessity for further reforms to eliminate remaining executive influence and promote a cohesive judicial framework, thereby reinforcing the rule of law and enhancing the credibility of the judiciary in Indonesia.